Avaliação dos efeitos tóxicos da exposição ao inseticida, fosforoamidotioato de O,S-Dimetila (Metamidofós) sobre o reflexo Bezold-Jarisch e sobre o quimiorreflexo em animais experimentais - Pinheiro, Gabriella Xavier Maretto (2012)
Poisoning by organophosphate pesticides is often accompanied by cardiac complications which may be serious and even fatal. However, the effects of these compounds on the cardiovascular mechanisms involved in blood pressure regulation remain unknown. The aim of this study was to evaluate the effects of the administration of a single sublethal dose (8 mg/kg, i.p.) of the organophosphorus insecticide methamidophos on the Bezold-Jarisch reflex (BJR) and on the chemoreflex, as well as the effects of this administration on the activity of the plasma cholinesterase (ChE), creatin kinase-MB (CK-MB) and lactate dehydrogenase (LDH). For the protocols involving the cardiovascular reflexes, male Wistar rats were treated with single intraperitoneal injections of methamidophos (8 mg/kg; n=23; MTF group) or saline (0.9%, n=20; control group, CON). Twenty four hours after the injection procedure the animals underwent catheterization of the femoral artery and vein to allow pressure recordings and drugs administration, respectively. Cardiovascular recordings were performed 24 hours after the catheterization procedures. The chemoreflex and BJR were activated by intravenous (i.v.) injections randomly assigned of KCN (10, 20, 40 and 80 µg/rat) and phenylbiguanide (PBG, 1.5, 3, 6, 12 and 24 µg/kg), respectively. The bradycardic responses of the BJR were expressed as % of fall compared to baseline levels, while the chemoreflex responses were expressed as delta mean arterial pressure and heart rate. Separated groups of rats were treated similarly for the protocols involving measurement of the ChE (n=10/group), CK-MB (n=10/group) and LDH (n=9/group) and blood samples collected 24 h after the treatment. The statistical analysis used for the cardiovascular reflexes was one-way ANOVA for repeated measures followed by the Fisher's post hoc test and for the enzymatic protocols was the Student's t-test. The bradycardic component of the chemoreflex and of the BJR was significantly attenuated in animals treated with methamidophos. Similarly, the cholinesterase activity was significantly reduced in animals treated with this compound. However, no statistical differences were observed in the CK-MB and LDH activities between the studied groups (CON and MTF). Our data show that the acute treatment with methamidophos impairs the function of two cardiovascular reflexes, which could contribute to the cardiovascular complications observed in the acute poisoning by these compounds.